7 - Peasant Agriculture, Commercial Production and Employment in Kenya - Moody, Tony (Africa Development, 1976)
This paper attempts to assess the significance of commercial crop production to peasant agriculture in Kenya, and the implications it has for rural employment aspirations. The assessment is based on a recent study the author made in the Nyanza Province of Kenya, a study of peasant agricultural produc- tion based on analyses of historical data and sample surveys